Análisis del cumplimiento tributarío de una empresa de servicios de transporte marítimo internacional “naviera s.a” ubicado en la ciudad de Guayaquil, durante el ejercicio fiscal correspondiente al año 2008 - Cajamarca Ortiz, Michelle (2010)
To study the role of our graduate thesis we have taken the theme "ANALYSIS OF A BUSINESS TAX COMPLIANCE SERVICES INTERNATIONAL SHIPPING NAVIERA SA LOCATED IN THE CITY OF GUAYAQUIL, DURING THE FISCAL YEAR 2008" as indicated our work has been to make the analysis of the documentation provided by Naviera SA, according to the requirements of Generally Accepted Accounting Principles, the Ecuadorian Accounting Standards, the Internal Tax Law Regime, the Customs Act, and other agreements and regulations in order to express an opinion on compliance. In our thesis you will be able to appreciate the description of the company, its main processes and the macroeconomic environment around it. We carried out a study of the company position represented by graphs and time line. Our audit was carried out by gathering necessary information and tests have been applied in compliance by auditors to obtain real information that will reflect in the Audit Report. As a result, developed the tax audit report with all the formalities of the law, we must emphasize that confidentiality of the information obtained, the name of the company was assigned as part of our intellectual property